MATHEMATICAL MODELS OF THE TRANSPORT SYSTEM BASED ON C-ITS SECURITY - Djurayev Sherzod Sobirjonovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Connected and Intelligent Transportation Systems (C-ITS) are revolutionizing the way we manage and operate transport systems. However, with the increasing integration of digital technologies into transportation infrastructure, security becomes paramount. This article explores the development and application of mathematical models to enhance the security of C-ITS within the transport system. We discuss the key challenges, solutions, and implications of securing C-ITS and propose a roadmap for future research in this domain.